1990
DOI: 10.1111/j.1467-9817.1990.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of syntactic simplification on reading EST texts as L1 and L2

Abstract: There has been a considerable suggestion in the literature that syntactic adaptation of a text would simplify it. This empirical study determined that the complexity of the syntax does not significantly affect the level of reading comprehension. While a complete conceptual and lexical analysis may be necessary for reading comprehension, a thorough syntactic analysis is not. This should be true for both expert and novice readers in a particular professional field, herein computer science.Using American (L1 or E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Examples include: the use of illustrations (Halbert 1944, Vernon 1946, Omaggio 1979Felker et al, 1981), schemas (Rumelhart 1984), structural cues (Spyridakis, 1989(Spyridakis, , 1989a, highlighting (Klare et al 1955b, Felker et al), paragraph length (Markel, et al, 1992), typographic format , syntax simplification (Ulijn and Strother 1990), prior knowledge (Richards 1984), nominalizations, diagrams, parallelism, white space, line graphs, and justified margins (Felker et al,), "whiz deletions" (Huckin et al 1991), writer guidelines (McLean 1985), and coherence and cohesion (Freebody andAnderson 1983, Halliday andHasan 1976).…”
Section: A Community Of Scholarsmentioning
confidence: 99%
“…Examples include: the use of illustrations (Halbert 1944, Vernon 1946, Omaggio 1979Felker et al, 1981), schemas (Rumelhart 1984), structural cues (Spyridakis, 1989(Spyridakis, , 1989a, highlighting (Klare et al 1955b, Felker et al), paragraph length (Markel, et al, 1992), typographic format , syntax simplification (Ulijn and Strother 1990), prior knowledge (Richards 1984), nominalizations, diagrams, parallelism, white space, line graphs, and justified margins (Felker et al,), "whiz deletions" (Huckin et al 1991), writer guidelines (McLean 1985), and coherence and cohesion (Freebody andAnderson 1983, Halliday andHasan 1976).…”
Section: A Community Of Scholarsmentioning
confidence: 99%
“…This was chosen as the main variable of the study because reading materials constitute a very important factor in reading comprehension tests. Background knowledge, for example, is a well-researched area (see for example: Alderson and Urquhart 1983, 1985a, 1985bBernhardt 1991;Carrell and Eisterhold 1983;Clapham 1996;Johnson 1981Johnson , 1982Mohammed and Swales 1984;Salager-Meyer 1991;Steffensen and Joag-Dev 1984;Steffensen, Joag-Dev and Anderson, 1979;Ulijn and Strother 1990). Of the various factors, the choice of texts with a focus on authentic versus inauthentic was chosen for this investigation.…”
Section: Selection Of Texts: the Nature Of Inputmentioning
confidence: 99%
“…However, other research has shown that syntactic complexity is not an issue in reading outcomes, particularly for high-proficiency learners (Eslami, 2014;Oh, 2001;Strother & Ulijn, 1987;Ulijin & Strother, 1990). Eslami (2014) in a text modification study found that highproficiency learners were unaffected by modifications in text syntactic complexity while low and mid-proficiency learners were affected, as reflected in higher scores on syntactically simplified texts.…”
Section: The Nature Of the Role Of Textual Features In L2 Reading Outmentioning
confidence: 99%
“…contexts (Strother & Ulijn, 1987;Ulijin & Strother, 1990). However, the experimental groups were classified as advanced L2 level so, the researchers assumed that syntactic simplification or syntactic complexity may have an effect on limited proficiency language users (Ulijin & Strother, 1990).…”
Section: Text Syntactic Complexity and L2 Reading Outcomesmentioning
confidence: 99%
See 1 more Smart Citation